A Case Study of an Antibiotic Discovery Laboratory Autonomous Learning Assignment—An Evaluation of Undergraduate Students’ Disciplinary Bias - Nadav Badrian; Lilach Iasur-Kruh; Yael Ungar; Iris Sonia Weitz (Education Sciences, 2024)
Current higher education trends are moving towards interdisciplinary curricula to provide new tools for solving complex issues. However, course design and learning tracks still create divisions between scientific disciplines. This study aimed to evaluate the disciplinary bias of second-year undergraduate students of biotechnology engineering in the organic chemistry laboratory class through a laboratory setting involving blended disciplines. An experiment on antibiotic discovery that integrates parallel and combinatorial organic chemistry syntheses with microbiology techniques was chosen. As a part of an activity, students had free choice in designing the arrangement of the organic compounds and the two bacterial species by setting up the layout for a 96-well plate. The study visually analyzed students’ plate layouts (n = 74) according to discipline classification and the spatial arrangements of organic compounds (e.g., products and libraries). The results identified four themes that are suggested to reflect students’ vertical, lateral, and interdisciplinary thinking, as most were found to be in the procedural knowledge range and between Bloom’s application and analysis dimensions. Using this study’s thematic analysis methodology in chemistry and related educational fields can provide a pedagogical reflective tool and advance personalized teaching and interdisciplinarity.